Simulated annealing based VM placement strategy to maximize the profit for Cloud Service Providers; Engineering Science and Technology, an International Journal; Vol. 20, iss. 4 - Sourav K. A. Kanti Addya; Ashok T. Turuk; Bibhudatta S. Sahoo; Mahasweta S. Sarkar; Bisvas S. K. Sanzhay Kumar (2017, 2017)
Title screen